PEMANFAATAN ABU TONGKOL JAGUNG SEBAGAI ALTERNATIF KATALIS BASA PADA PEMBUATAN BIODIESEL DARI MINYAK JELANTAH - Risna Adu (Fakultas Pertanian, Universitas Timor, 2020)
The utilization of corncob ash as an alternative base catalyst source for biodiesel production has been studied to determine the corn cob's ash potential in transesterification proccess from waste cooking oil. Corn cob ash properties was analyzed by AAS and alkalinity test to measured potassium levels and its form. Alkaline solution was obtained by stirring corn cobs ash in methanol for 4 hours. Transesterification of waste cooking oil was carried out by varying ash amount for 5, 10, 15, and 20 g (molar ratio of methanol/oil 6:1 at 60 oC for 2 hours and stirring speed was kept constant); and methanol /oil molar ratio for 3: 1, 6: 1, 9: 1 and 12: 1 (optimum amount of ash). Methyl esters content was determined by GC-MS, while some physical and chemical properties of biodiesel were measured using the ASTM standard method. Potassium content of corncob ash was 38.76% (wt), the potassium might be presence in carbonate form. Optimum condition of biodiesel conversion was reached at the use of 10 gr corn cob ash and methanol/oil molar ratio of 6: 1. GC-MS data showed that biodiesel from waste cooking oil are methyl esters which are dominated by methyl linoleate and methyl palmitate. The quality of biodiesel products (viscosity and density) meets the requirements of biodiesel specifications according to SNI 7182-2015. Corn cobs ash can be used as an alternative basic catalyst source for biodiesel transesterification. On the other side waste cooking oil and corn cobs value can be improved by using them in the transesterification process.